THE SPIRITUALITY OF MAHOBATLI PAINTING WORKS IMPORTANCE (Archive of Conferences, 2022)
Monumental pictorial art is one of the boundlessly in our society. Monumental pictorial art is complication intellect- intuiton, thought, vast-smoll alteration eventin nature, uninterrupted philosophuy ideas and it can express fantasy. They are an essential for to educate currently person on patriotism.